Reading Quraish Shihab's Oral Exegesis About glorifying Women In Social Media - M. Riyan Hidayat; Ahmad Murtaza MZ (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2022)
Abstract This paper will explain the oral interpretation of Quraish Shihab about glorifying women on social media on the Shihab N Shihab program which is monitored by one of his daughters, Najwa Shihab. The description will explain in the form of a descriptive analysis approach. The data is collected from recorded social media documentation and literature studies. Meanwhile, the theory that will be used in this research is the theory of oral exegesis, which was initiated by Andreas Gorke. The author concludes that the oral practice developed by Quraish Shihab has two faces, namely the context in the Qur'an and the hadith, while the second is the context outside the text of the Qur'an and hadith which is more social in society. Keywords: Glorifying Women, Quraish Shihab, Oral Exegesis Abstrak Tulisan ini akan menjelaskan tafsir oral dari Quraish Shihab tentang memuliakan perempuan di media sosial pada program Shihab N Shihab yang dimonitori oleh salah satu putri nya Najwa Shihab. Uraian akan menjelaskan dalam bentuk pendekatan deskriptif analisis. Datanya dikumpulkan dari dokumentasi rekaman media sosial dan studi pustaka. Sedangkan teori yang akan digunakan dalam penelitian ini adalah teori tafsir oral (oral exsegesis) yang digagas oleh Andreas Gorke. Penulis menyimpulkan bahwa praktek oral yang dibangun oleh Quraish Shihab dua wajah yakni Konteks di dalam al-Qur’an dan hadis sedangkan yang kedua konteks diluar teks al-Qur’an dan hadis yang lebih mengarah pada sosial bermasyarakat. Kata kunci: Memuliakan Perempuan, Quraish Shihab, Tafsir Oral